2000
DOI: 10.1021/bi992705n
|View full text |Cite
|
Sign up to set email alerts
|

GCN4 Binds with High Affinity to DNA Sequences Containing a Single Consensus Half-Site

Abstract: bZip proteins contain a bipartite DNA-binding motif consisting of a "leucine zipper" dimerization domain and a highly charged "basic region" that directly contacts DNA. These transcription factors form dimeric complexes with each monomer recognizing half of a symmetric or nearly symmetric DNA site. We have found that the bZip protein GCN4 can also bind with high affinity to DNA sites containing only a single GCN4 consensus half-site. Because several recent lines of evidence have suggested a role for monomeric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
53
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(66 citation statements)
references
References 83 publications
(176 reference statements)
13
53
0
Order By: Relevance
“…This is in agreement with measurements by Hollenbeck and Oakley, who measured a 10-fold decrease in half-site binding (38). In related studies, other labs have found that monomeric and dimeric GCN4 bZIP bind similarly and strongly to their target half and full sites (41)(42)(43).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…This is in agreement with measurements by Hollenbeck and Oakley, who measured a 10-fold decrease in half-site binding (38). In related studies, other labs have found that monomeric and dimeric GCN4 bZIP bind similarly and strongly to their target half and full sites (41)(42)(43).…”
Section: Resultssupporting
confidence: 92%
“…For example, little or no induction of helicity in bZIP derivatives upon addition of nonspecific DNA has been observed in some cases (44,45). However, Hollenbeck and Oakley found that their nonspecific DNA control induced comparable helicity in their GCN4 bZIP derivative as did the native AP-1 and CRE sites (38). Regardless of strength of thermodynamic binding affinity, all of the sites that we examined by CD can preorganize R-helical structure, and there appears to be no clear relationship between binding affinities and structural stabilization.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that homodimeric peptides based on GCN4 which contain both the conserved basic and zipper domains, display similar binding affinities for CRE, AP1 and half-CRE DNA. [59] A slight increase in the helicity of (GCN4bd) 2 and bipy-(GCN4bd) 2 is observed in their CD spectra recorded in the presence of either AP1 or half-CRE DNA, similar to that in the presence of CRE DNA (but in the absence of metal ions), and to previous reports ( Figure 7 A and B).…”
Section: Dna Sequence Selectivitysupporting
confidence: 88%
“…3b, lanes 1-3, and 7-9). These bands with the non-consensus dsDNAs are more diffuse than those observed with the direct DNA, and most probably arise from a relatively loose complex in which one of the basic regions is interacting specifically in the major groove of the consensus site while the other makes nonspecific contacts 38 . Curiously, the control disulphide (3b) 2 SS, in which the terpyridine was replaced by an inert chromophore, did not elicit such interactions with the non-consensus DNAs (Fig.…”
Section: Resultsmentioning
confidence: 88%